2011
DOI: 10.1021/np100843j
|View full text |Cite
|
Sign up to set email alerts
|

Stereostructure Reassignment and Determination of the Absolute Configuration of Pericosine Do by a Synthetic Approach

Abstract: A combination of chemical synthesis and NMR methods was used to reassign the structure of pericosine D(o) (8), a cytotoxic marine natural product produced by the fungus Periconia byssoides OUPS-N133 that was originally derived from the sea hare Aplysia kurodai. Chemical synthesis was used to prepare pericoisne D(o) (8) from a known chlorohydrin that was in turn derived from (-)-quinic acid. The absolute configuration of natural pericosine D(o) (8) was determined to be methyl (3R,4S,5S,6S)-6-chloro-3,4,5-trihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…305,306 Synthesis and NMR spectroscopic analysis were used to reassign the structure and determine the absolute conguration of pericosine D 0 , a metabolite of the sea hare-derived fungus Periconia byssoides, 307 as methyl (3R,4S,5S,6S)-6-chloro-3,4,5-trihydroxy-1-cyclohexene-1-carboxylate 403. 308 Synthesis of the proposed structure of phomopsin B, 309 a metabolite of the mangrove endophytic fungus Phomopsis sp., led to revision of the structure to that of the known dothiorelone A, previously isolated from another mangrove endophytic fungus Dothiorella sp. 310 Total synthesis of dothiorelone A/phomopsin B through a cross-metathesis with a chiral olen was then completed.…”
Section: Synthetic Aspectsmentioning
confidence: 99%
“…305,306 Synthesis and NMR spectroscopic analysis were used to reassign the structure and determine the absolute conguration of pericosine D 0 , a metabolite of the sea hare-derived fungus Periconia byssoides, 307 as methyl (3R,4S,5S,6S)-6-chloro-3,4,5-trihydroxy-1-cyclohexene-1-carboxylate 403. 308 Synthesis of the proposed structure of phomopsin B, 309 a metabolite of the mangrove endophytic fungus Phomopsis sp., led to revision of the structure to that of the known dothiorelone A, previously isolated from another mangrove endophytic fungus Dothiorella sp. 310 Total synthesis of dothiorelone A/phomopsin B through a cross-metathesis with a chiral olen was then completed.…”
Section: Synthetic Aspectsmentioning
confidence: 99%
“…Structural determinations of pericosines D and D o were not straightforward [64][65][66]85]. Isolation of pericosine D was reported in 1999 at the Annual Meeting of the Pharmaceutical Society of Japan, and the structure was reported as 26 [85].…”
Section: Syntheses Of Pericosines Strating From D-ribose Via Ring-clomentioning
confidence: 99%
“…But synthetic 6 had the same retention time as natural 6 in the chiral HPLC analysis. A detailed description on the chiral HPLC analysis will be given below [66]. Since the specific rotation of synthesized (À)-6 had the opposite sign ([a] D 25 À6.5) to the reported natural pericosine D o ([a] D þ1.9), the specific rotation of natural 6 was remeasured, giving an acceptable [a] D 25 value of À6.6, which suggested that the absolute configuration of natural pericosine D o was (3R,4S,5S,6S)-6-chloro-3,4,5-trihydroxy-1-cyclohexene-1-carboxylate (6).…”
Section: Syntheses Of Pericosines Strating From D-ribose Via Ring-clomentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of our continuing studies on the synthesis of bioactive marine natural products, we have studied and reported on the total syntheses of pericosines [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Pericosines A–E ( 1 – 6 ) are unique carbasugar-type metabolites of the fungus Periconia byssoides OUPS-N133, which was originally isolated from the sea hare Aplysia kurodai [ 16 , 17 , 18 ]. As pericosine A ( 1 ) showed remarkable anticancer activity, several other research groups have also undertaken and reported the syntheses of pericosines [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%